Rosie Revere, Engineer - Beaty, Andrea; Roberts, David 1970- (New York : Abrams Books for Young Readers, 2013)
A young aspiring engineer must first conquer her fear of failure.
Keywords: Stories in rhyme; Engineers -- Juvenile fiction; Inventions -- Juvenile fiction; Failure (Psychology) -- Juvenile fiction; Perseverance (Ethics) -- Juvenile fiction; Stories in rhyme; Engineers -- Fiction; Inventions -- Fiction; Failure (Psychology) -- Fiction; Perseverance (Ethics) -- Fiction